Metamaterial Inspired Patch Antenna for ISM Band by Adding Single-Layer Complementary Split Ring Resonators - Rajni Rajni; Gursharan Kaur; Anupma Marwaha (International Journal of Electrical and Computer Engineering (IJECE), 2015)
In this work, we propose the design of metamaterial inspired compact circular patch antennas loaded with complementary split-ring resonators (CSRRs) for ISM band operation. CSRRs have been incorporated horizontally inside the dielectric. The various models of CSRR loaded antennas with different patch radius are produced and are evaluated numerically with Ansoft HFSS software. The results of the suggested antenna designs are presented that reveal a comparable impedance match and radiation characteristics with those of a normal patch antenna without CSRR. The proposed antennas yield high levels of miniaturization and similar performance to the conventional patch antenna at the 2.45GHz.